Synthesis, characterization, anti-trypanosomal activity and toxicity against Artemia salinaLeach of thiobenzamides and derivatives - Finagnon H. Agnimonhan, Leon Ahoussi, Salome D. S. Kpoviessi, Fernand A. Gbaguidi, Coco N. Kapanda, Joanne Bero, Veronique Hannaert, Joelle Quetin-Leclercq, Mansourou Moudachirou, Jacques Poupaert, Georges C.Accrombessi (Journal of Applied Pharmaceutical Science)
This work aims to synthesize, characterize of thioamides benzaldehyde and 4-(dimethylamino)benzaldehyde and assess their in votrotrypanocidal activity and totoxicity. The Willgerodt-Kindler reaction preferred for the synthesis of thioamides morpholin-4-yl (phenyl) methanethione 1 and [4 - (dimethylamino) phenyl] - (morpholin-4-yl) methanethione 2, is catalyzed with montmorillonite K-10 and in a microwave oven. The structures of the thioamides were characterized and confirmed by IR spectrometry, nuclear magnetic resonance (1H and 13C NMR) and mass spectrometry (MS) Their trypanocidal activity was evaluated in the blood stream form of the strain of Trypanosoma brucei brucei 427 using the 'Lilit, Alamar Blue' (Baltz et al., 1985; Hirumi et al., 1994; Räz et al., 1997) and cytotoxicity on brine shrimp larvae (Artemia salina Leach) using the method of Michael et al. (1956) resumed by Vanhaecke et al. (1981) and Sleet and Brendel (1983). The compounds1 (IC50> 483.09 µM) and 2 (IC50> 400 µM) have weak trypanocidal activities. However the larvae were sensitive to 2 (LD50 = 214 ± 9 µM) and therefore it could be used in cancer treatment.
Keywords: Willgerodt-Kindler,Montmorillonite K-10,morpholin-4-yl (phenyl)-methanethione,[4-(di-methylamino) phenyl] (morpholin-4-yl) methanethione,Artemia salina Leach,trypanocidalINTRODUCTION